Influence of atmospheric modes of variability on the limnological characteristics of large lakes south of the Alps: a new emerging paradigm - Salmaso, N; Buzzi, F; Cerasino, L; Morabito, G; Rogora, M; Simona, M.; GARIBALDI, LETIZIA; LEONI, BARBARA (Hydrobiologia, 2014)
Winter air and spring surface water temperatures, spring epilimnetic phosphorus, and hypolimnetic oxygen in the deep lakes south of the Alps (Garda, Iseo, Como, Lugano, and Maggiore) showed a high degree of temporal coherence. The common temporal patterns were originating from the effects caused by winter climate, and from corresponding synchronisms in the interannual variations in the extent of the spring water renewal and replenishment of nutrients. In turn, the sequence of linked causal events was triggered by two atmospheric modes of variability relevant for the Mediterranean region, i.e. the East Atlantic pattern (EA) and the Eastern Mediterranean Pattern (EMP). In contrast, there were no significant relationships of air and water temperatures with the North Atlantic Oscillation. In oligotrophic lakes, which were characterised by weak vertical nutrient gradients, the spring replenishment of P was negligible and difficult to detect (Maggiore), or detectable but of minor importance (Garda and Como) compared to that measured in more enriched lakes (Iseo and Lugano). The applicability of EA and EMP in the study of the impact of climate on aquatic ecosystems will require to be tested by expanding the number, typology, and geographical location of water bodies in the Alpine and Mediterranean regions